Oral function is associated with the body and muscle mass indices of middle‐aged dental patients - Tomotaka Nishi; Midori Ohta; Tomofumi Takano; Koichiro Ogami; Takayuki Ueda; Kaoru Sakurai (Wiley, 2022)
Abstract Objectives Undernutrition is associated with frailty, one of the common reasons for seeking long‐term care. In older adults, nutritional status is known to be associated with oral function; however, it is not yet known if there is a similar association in middle‐aged adults. The present study determined the association between nutritional status and oral function in middle‐aged adults. Material and methods This cross‐sectional study was conducted in 117 outpatients aged 40-64 years who underwent dental check‐up at a private dental clinic. Factors associated with oral function, including oral moisture, number of teeth present, oral diadochokinesis, tongue pressure, lip‐seal strength, and masticatory performance, were evaluated. Body mass index (BMI), fat‐free mass index (FFMI), and skeletal muscle mass index (SMI) were analyzed as nutritional statuses. Pearson's correlation analysis was conducted to determine the correlation between nutritional statuses and other variables. Multiple linear regression analysis was performed, with adjustment for age and sex, using BMI, FFMI, or SMI as response variables and oral moisture, maximum tongue pressure, lip‐seal strength, oral diadochokinetic rate, and masticatory performance as explanatory variables. Results All nutritional statuses showed significant correlation with maximum tongue pressure and lip‐seal strength. Multiple linear regression analysis revealed that BMI was associated with maximum tongue pressure and lip‐seal strength, whereas FFMI and SMI showed significant association with sex, maximum tongue pressure, and lip‐seal strength. Conclusions In middle‐aged outpatients at a regional dental clinic, lip‐seal strength and tongue pressure were positively associated with BMI, FFMI, and SMI.